Concepts, terms and symbols in mathematics textbooks - Norvaiša, Rimas (Lietuvos matematikos rinkinys, 2023)
The article discusses the problems of definitions of concepts of school mathematics in textbooks. Excerpts from textbooks show how interpretations of a fraction having no necessary properties of a mathematical definition have changed over the decades. The alternative of a concept of a fraction based on the number line is discussed.